Fitz Hugh Curtis syndrome as a cause of acute abdomen: case report - Gutiérrez, Carlos Durán; Rojas, Andres Felipe Alvarez; Muñoz, Braulio Rios (International Journal of Research in Medical Sciences, 2023)
The case of a young adult woman who came to the emergency room with acute surgical abdomen is presented. As part of her treatment, laboratory studies were performed, highlighting leukocytosis at the expense of neutrophilia. An abdominal CT study with contrast was also performed, which showed free fluid in the abdominal cavity without diagnostic confirmation, so a diagnostic laparoscopy was performed where perihepatic adhesions were evident on violin strings suggestive of Fitz Hugh Curtis syndrome. Fitz Hugh Curtis syndrome is an entity little reported in the surgical literature. Its manifestations are nonspecific with generalized abdominal pain, nausea, vomiting, and fever. It is a diagnostic challenge since it can be confused with other surgical gastrointestinal pathologies such as appendicitis or cholecystitis, occurs in both genders, although it is more common in women of reproductive age, its diagnosis is usually a postoperative finding, the prognosis will depend on the postoperative findings and non-surgical management. We present a review of the literature and a reported case.